Genetic view on intelligence and its heredity - Wasielewska, Magdalena; Bethke, Krzysztof (Journal of Education, Health and Sport, 2019)
Introduction : Intelligence is a term that has aroused human curiosity for hundreds of years. Many researchers have tried to define its definition, but have not yet succeeded in creating a single definition. Its genetic background has been the subject of much scientific researches in recent times. Aim : Research on twins and their parents allowed scientists to prove the influence of genes on cognitive processes and discover the fact that the level of intelligence depends on genetic factors. State of knowledge : It is also known, however, that there is a phenomenon of regression to the average, which means that a couple with high intellectual abilities on average have offspring with a lower level of intellect than the parents themselves. Intelligence genes are genes of the dopaminergic system such as DRD2, DRD4, SLC6A3, CCKAR, adrenergic e.g. ADRB2 and neurotrophin genes, i.e. BDNF and also those whose products cooperate in combating free radicals - LTF and PRNP. Gene polymorphisms, i.e. differences in DNA among populations, play an important role in shaping the level of intelligence. Depending on the presence of polymorphisms, some IQ genes decrease or increase. Research is still underway to discover further differences in DNA intelligence levels modulation. Many of them show to have a beneficial relationship with intelligence.For example, the cD.957C> T polymorphism of the DRD2 gene if thymine was at the polymorphic site, the ADRB2 c.46A> G gene if guanine and BDNF were present when guanine was at c.472G> A position.Conclusions : The obtained results prove that intelligence is a complex trait, which is influenced by genetic and environmental factors.